prevalence of Tapeworm Infestation in Chickens in Hama governorate (Journal of Hama University, 2021)
Cestodiasis in Poultry is a limited disease due to modern breeding systems and because it requires an intermediate host to complete its life cycle, this makes it more prevalent in the free education areas than in the intensive education areas.These parasites lead to great economic losses as a result of depleting the bird's food and reducing its production efficiency.Tracking was carried out on 67 poultry farms spread in 20 regions in Hama Governorate, whose ages ranged between 2 – 78 weeks and with different types (Laying hens - Breeders - Broilers - Native chickens), where positive conditions were observed in some of the herds, which gives a perception about the weakness of these farms in protecting their herds from the parasite's access to it due to its need for medium mammals from arthropods and others ... which indicate their presence on the farm on the low level of protection.Rates of real injuries in breeders and laying hens compared to municipal chicken flocks P = 0.00001 However, no significant differences were observed between the breeders and laying hens P> 0.05 It was also noted the emergence of cases throughout the year, which is linked to the availability of a favorable environment for the intermediate host of the infected larval stage.